New source report: Chemical constituents of Hypericum quartinianum (Hypericaceae), a sub-Saharan African plant species. (August 2019) - Fobofou, Serge A.T.; Ares, Kaleab; Arnold, Norbert; Imming, Peter
Highlights: First phytochemical study of Hypericum quartinianum . Investigation of African Hypericum species of the section Campylosporus. Discussion of the chemotaxonomic significance of the isolated compounds.